A prospective evaluation of health‐related quality of life after skull base re‐irradiation. Issue 3 (23rd December 2019) - Bahig, Houda; Ng, Sweet P.; Pollard, Courtney; Nguyen, Theresa P.; Gunn, Gary B.; Rosenthal, David I.; Fuller, Clifton D.; Frank, Steven J.; Garden, Adam S.; Reddy, Jay P.; Morrison, William H.; Ferrarotto, Renata; et al.
Abstract: Purpose: To report cancer control outcomes and health‐related quality of life (HRQoL) outcomes after highly conformal skull‐based re‐irradiation (re‐RT). Methods: Patients planned for curative intent re‐RT to a recurrent or new skull base tumor were enrolled. HRQoL were assessed using the MD Anderson Symptom Inventory Brain Tumor (MDASI‐BT) and the anterior skull base surgery quality of life (ASBQ) questionnaires. Results: Thirty‐nine patients were treated with stereotactic body RT or intensity modulated RT. Median follow‐up was 14 months. Progression free survival was 71% at 1‐year. There was mild clinically significant worsening of fatigue, lack of appetite and drowsiness (MDASI‐BT), and physical function (ASBQ) at the end of RT, followed by recovery to baseline on subsequent follow‐ups. Subjective emotions were clinically improved at 12 months, with patients reporting feeling less tense/nervous. Conclusion: Conformal skull base re‐RT is associated with mild immediate deterioration in physical function followed by rapid and sustained recovery.